Understanding disadvantaged adolescents' perception of health literacy through a systematic development of peer vignettes - Hannah R. Goss; Clare McDermott; Laura Hickey; Johann Issartel; Sarah Meegan; Janis Morrissey; Celine Murrin; Cameron Peers; Craig Smith; Ailbhe Spillane; Sarahjane Belton (BMC, 2021)
Abstract Background Adolescence represents a crucial phase of life where health behaviours, attitudes and social determinants can have lasting impacts on health quality across the life course. Unhealthy behaviour in young people is generally more common in low socioeconomic groups. Nevertheless, all adolescents should have a fair opportunity to attain their full health potential. Health literacy is positioned as a potential mediating factor to improve health, but research regarding health literacy in adolescents and socially disadvantaged populations is limited. As part of Phase one of the Ophelia (OPtimising HEalth LIterAcy) framework, The purpose of this study was to explore the perceptions of socially disadvantaged Irish adolescents in relation to health literacy and related behaviours, and utilise this data to develop relevant vignettes. Methods A convergent mixed method design was used to co-create the vignettes. Questionnaires were completed by 962 adolescents (males n = 553, females n = 409, Mean age = 13.97 ± 0.96 years) from five participating disadvantaged schools in Leinster, Ireland. Focus groups were also conducted in each school (n = 31). Results were synthesised using cluster and thematic analysis, to develop nine vignettes that represented typical male and female subgroups across the schools with varying health literacy profiles. These vignettes were then validated through triangular consensus with students, teachers, and researchers. Discussion The co-creation process was a participatory methodology which promoted the engagement and autonomy of the young people involved in the project. The vignettes themselves provide an authentic and tangible description of the health issues and health literacy profiles of adolescents in this context. Application of these vignettes in workshops involving students and teachers, will enable meaningful engagement in the discussion of health literacy and health-related behaviours in Irish young people, and the potential co-designing of strategies to address health literacy in youth. Conclusion As guided by the Ophelia framework, the use of authentic, interactive and participatory research methods, such as the co-creation of vignettes, is particularly important in groups that are underserved by traditional research methods. The approach used in this study could be adapted to other contexts to represent and understand stakeholders' perceptions of health, with a view to explore, and ultimately improve, health literacy.